Fall Armyworm Gut Bacterial Diversity Associated with Different Developmental Stages, Environmental Habitats, and Diets - Dan-Dan Li; Jin-Yang Li; Zu-Qing Hu; Tong-Xian Liu; Shi-Ze Zhang (Insects, 2022)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), is a major invasive pest that seriously threatens world agricultural production and food security. Microorganisms play a crucial role in the growth and development of insects. However, the diversity and dynamics of gut microbes with different developmental stages, environmental habitats, and diets in S. frugiperda remain unclear. In this study, we found the changes of the microbiome of S. frugiperda across their life stages, and the bacteria were dominated by Firmicutes and Proteobacteria. The community composition of the egg stage was quite different from other developmental stages, which had the highest community diversity and community richness, and was dominated by Proteobacteria. The bacterial community compositions of male and female adults were similar to those of early larvae stage (L1–L2), and operational taxonomic units (OTUs) with abundant content were Enterococcus and Enterobacteriaceae bacteria, including Enterobacteria, Klebsiella, Pantoea, and Escherichia. The third instar larvae (L3) mainly consist of Enterococcus. The late stage larvae (L4–L6) harbored high proportions of Enterococcus, Rhodococcus, and Ralstonia. There was no significant difference in gut microbial composition between field populations and laboratory populations in a short period of rearing time. However, after long-term laboratory feeding, the gut microbial diversity of S. frugiperda was significantly reduced. Enterococcus and Rhodococccus of S. frugiperda feeding on maize showed higher relative proportion, while the microbial community of S. frugiperda feeding on artificial diet was composed mainly of Enterococcus, with a total of 98% of the gut microbiota. The gene functions such as metabolism, cell growth and death, transport and catabolism, and environmental adaptation were more active in S. frugiperda feeding on corn than those feeding on artificial diet. In short, these results indicate that developmental stage, habitat, and diet can alter the gut bacteria of S. frugiperda, and suggest a vertical transmission route of bacteria in S. frugiperda. A comprehensive understanding of gut microbiome of S. frugiperda will help develop novel pest control strategies to manage this pest.